Xiaoyaosan Ameliorates Chronic Restraint Stress-Induced Depression-Like Phenotype by Suppressing A2AR Signaling in the Rat Striatum - Zhu, Xiaoxu; Ma, Qingyu; Yang, Furong; Li, Xiaojuan; Liu, Yueyun; Chen, Jianbei; Li, Lan; Chen, Man; Zou, Xiaojuan; Yan, Li; Chen, Jiaxu (Frontiers in Pharmacology, 2022)
Depression is a common mental disorder characterized by pessimism and world-weariness. In our previous study, we found that Xiaoyaosan (XYS) could have antidepressive effects, however the underlying mechanisms remain unclear. Several studies have shown that adenosine A(2A) receptor (A2AR) in the brain is a key point in the treatment of depression. Our present study aimed to investigate the effects of XYS on A2AR signaling in the striatum of rats exposed to chronic restraint stress (CRS). Ninety-six male Sprague–Dawley rats were randomly divided into 8 groups (control, model, negative control, XYS, A2AR antagonist, A2AR antagonist + XYS, A2AR agonist, A2AR agonist + XYS). The rats in the model group, XYS group, A2AR antagonist group and A2AR antagonist + XYS group were subjected to CRS for 3 hours a day. The XYS decoction [2.224 g/(kg·d)] was intragastrical administered by oral gavage to the rats in the negative control group, XYS group, A2AR antagonist + XYS group, and A2AR agonist + XYS group. The rats in the A2AR antagonist group and A2AR antagonist + XYS group were treated with SCH 58261 [0.05 mg/(kg·d)], and the rats in the A2AR agonist and A2AR agonist + XYS group were treated with CGS 21680 [0.1 mg/(kg·d)]. These procedures were performed for 21 consecutive days. Behavioral studies including the open field test, elevated plus maze test, sucrose preference test and forced swimming test, were performed to examine depression-like phenotypes. Then, the effects of XYS on CRS- or A2AR agonist-induced striatal subcellular damage, microglial activation and A2AR signaling changes in the striatum were examined. Here, we report that XYS ameliorates depression-like phenotypes (such as body weight loss as well as depression- and anxiety-like behaviors) and improves synaptic survival and growth in the stratum of the CRS rats. Moreover, XYS reduces A2AR activity and suppresses hyper-activation of striatal microglia. The tissue and cellular effects of XYS were similar to those of the known A2AR antagonists. In conclusion, XYS alleviates depression in the CRS rats via inhibiting A2AR in the striatum.